Tudang Sipulung: A Conflict Resolution Wisdom of Bugis-Makassar Community - Nuh, Muhammad Syarif (Hasanuddin Law Review, 2016)
This article explores local wisdom âtudang sipulungâ (seated together), as conflict settlement medium of Bugis-Makassar Community of South Sulawesi, Indonesia.Tudang sipulung is one of the social institutions that owned the Bugis-Makassar South Sulawesi as a conflict resolution. Tudang sipulung was originally only known in the agricultural community in resolving conflicts related to agriculture, and developing relevant social disputes. Formally, this Tudang Sipulung accommodated by Police in South Sulawesi in the form of a forum called the Mabbulo Sibatang Communication Forum (FKMB) to resolve the conflict. FKMB essence is tudang sipulung between the government, the team of FKMB Police, religious leaders, community leaders, the parties to the dispute and sit together in solving the conflict. Some conflicts that have occurred and are resolved through conflict FKMB PTPN XIV Wajo regency with the community District Kera in Wajo regency, Conflict PTPN XIV Takalar with Gowa regency related to land use and conflict Execution University of AlâAsâyariah Mandar Polewali Mandar, West Sulawesi, Indonesia.